Isolation and Identification of Escherichia coli and Staphylococcus aureus from animal and detection of their antibiotics susceptibility pattern - B. Aldeewan, Ali (University of Thi-Qar Journal of Science, 2022)
Food-borne infections and diseases remain one of the major concerns of public health and food safety caused by a wide range of pathogens contaminating food and food products. Staphylococcal food poisoning is one of the most economically important foodborne diseases in public health programs worldwide while the most common and important species of Escherichia genus which consists of five species, these species that cause human infection. A total of 44 swab samples were collected from different animals (Cow, Buffalo, and Goat). These samples were collected from Al Qurnah farm, animal farm of Basrah veterinary collage. These samples were collected mainly from 4 locations in the animal body (nose, mouth, rectum, and vagina). The results indicates that the most E. coli isolation comes from the cows followed by goat and the most contaminated areas was mouth ( 100 % ) followed by nasal cavity ( 90.9 % ) , rectum ( 72% ) and finally vaginal cavity (54.5 %) while the results of S. aureus infected revealed that high percentage , were rectal samples (90.9%); nasal samples; (81.8%)and (72.7%) for both vaginal and oral samples. All animals were infected approximately equally with S. aureus. Antibiotic susceptibility test for E. coli concluded that the bacteria were sensitive to (Clindamycin, Cefoxirim and Erythromycin) and were resistance to Vancomycin and Tetracycline While Antibiotic susceptibility result for S. aureus showed susceptibility to Clindamycin, and Tetracycline and complete resistance to Cefotaxime and Vancomycin.